Perfil lipídico y consumo de frutas y verduras en un grupo de jóvenes de 10 a 19 años, según el índice de masa corporal (2015)
ABSTRACT: Childhood overweight is a pandemic that increases the risk of chronic non-communicable diseases. It has been estimated that being overweight is associated with metabolic disorders; even in early stages of life. However, it is necessary to establish whether this association is observed in Colombian population between 10-19 years old. Objective: To compare lipid profile and fruit and vegetable intakes, according to body mass index, in subjects aged 10-19 in a health insurance company (SURA) from Medellin. Methods: One hundred an three obese, 120 overweight, and 214 children with normal body mass index participated in a cross-sectional study. We compared total cholesterol, LDL-C, HDL-C and triglycerides between groups; at baseline and after 10-hour fasting period. Fruit and vegetable intakes were determined by 24-hour dietary record. Results: LDL-C levels in obese, overweight and control group were, respectively: 95 ± 32, 96 ± 53 and 80 ± 24 mg/dL (P = .000). Triglycerides levels in the same groups were: 116 ± 65, 112 ± 69 and 88 ± 52 mg/dL (P = .000). HDL-C levels in the 3 groups were: 52 ± 14, 53 ± 12 and 56 ± 14 mg/dL (P = .013). A significant inverse association between fruit intake and triglyceride levels in overweight participants was observed (P = .035). Fruit and vegetable intake were unusual. Conclusions: A high body mass index promotes an atherogenic lipid profile. It is necessary to implement actions to promote healthy habits associated with diet.